Peran Teknologi Informasi, Pemahaman Akuntansi Dan Kuantitas Kredit Dalam Menghasilkan Laporan Keuangan Berkualitas - Evi Juita Wailan' An (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research aimed to determine and analyze the influence of Information Technology, credit quantity and Accounting Comprehension in Producing a quality financial statement for Ministry of Micro, Small and Medium Enterprises in Medan City. The sampling method used in this research is simple random sampling. The total of the population in this research are 100 Ministry of Micro, Small and Medium Enterprises in Medan City. Research type used in this research is quantitative by testing the two-stage approach. The results of the analysis show that the Information Technology,and credit quantity has positive effect on quality financial statement. Accounting Comprehension not effect on quality financial statement.